Friday

August 1, 2014

August 1, 2014

Posted by **Skirby** on Monday, November 18, 2013 at 8:16pm.

Let F(x) be the antiderivative of f(x) with F(1)=0.

Then F(2) equals _____.

- Calculus -
**Reiny**, Monday, November 18, 2013 at 10:19pmWrite it as

f(x) = 7x^-2 - 6x^-6

F(x)= -7x^-1 + (6/5)x^-5 + c

F(2) = -7/2 + (6/5)/2^5 + c

= ......

- Calculus -
**Steve**, Tuesday, November 19, 2013 at 12:29amsince F(1) = 0, we have

-7 + 6/5 + c = 0

which you can plug in to evaluate F(2)

**Related Questions**

Calculus I - Consider the function f(x)=((2)/(x^2))-((3)/(x^5)). Let F(x) be the...

Calculus - Consider the function f(x)=(8)/(x^2)−(8)/(x^5) . Let F(x) be ...

Calculus - Consider the function f(x)=x^4 + 8sqrtx Let F(x) be the ...

math - Consider the function f(t)=2sec^2(t)–6t^2 . Let F(t) be the ...

Calculus (Antiderivatives) - Suppose f(x) is a continuous function. Then a ...

Math: Calculus - The velocity function is v(t)= t^2-5t+ 4 for a particle moving ...

calculus - antiderivative - can someone help me find the antiderivative of: f'(x...

calc - Consider the function f(t)=2sec^2(t)–10t^3. Let F(t) be the ...

Calculus - If f is the function defined by f(x)=(x^2+4x)^(1/3) and g is an ...

calculus - Find the most general antiderivative of the function 1) f(x)= (X^3)^1...